2019
DOI: 10.1002/sctm.18-0247
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Exploiting Unique Biological Features of Leukemia Stem Cells for Therapeutic Benefit

Abstract: Cancer stem cells play a critical role in disease initiation and insensitivity to chemotherapy in numerous hematologic malignancies and some solid tumors, and these stem cells need to be eradicated to achieve a cure. Key to successful targeting of cancer stem cells is to identify and functionally test critical target genes and to fully understand their associated molecular network in these stem cells. Human chronic myeloid leukemia (CML) is well accepted as one of the typical types of hematopoietic malignancie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…A recent study showed that dasatinib inhibits the phosphorylation of BCR-ABL without inducing the death of LSCs, suggesting that LSCs use signaling pathways that are activated by the BCR-ABL protein and are independent of its tyrosine kinase activity. The simple inhibition of the tyrosine kinase activity of the BCR-ABL protein is therefore not sufficient [199]. Since HDAC6 is overexpressed in CML stem cells and that its inhibition can potentially cause BCR-ABL degradation [68], this deacetylase appears as a strong candidate for CML treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that dasatinib inhibits the phosphorylation of BCR-ABL without inducing the death of LSCs, suggesting that LSCs use signaling pathways that are activated by the BCR-ABL protein and are independent of its tyrosine kinase activity. The simple inhibition of the tyrosine kinase activity of the BCR-ABL protein is therefore not sufficient [199]. Since HDAC6 is overexpressed in CML stem cells and that its inhibition can potentially cause BCR-ABL degradation [68], this deacetylase appears as a strong candidate for CML treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that dasatinib inhibits the phosphorylation of BCR-ABL without inducing the death of LSCs, suggesting that LSCs use signaling pathways that are activated by the BCR-ABL protein and are independent of its tyrosine kinase activity. The simple inhibition of the tyrosine kinase activity of the BCR-ABL protein is therefore not sufficient [192]. Since HDAC6 is overexpressed in CML stem cells and that its inhibition can potentially cause BCR-ABL degradation [68], this deacetylase appears as a strong candidate for CML treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Adequate understanding of LSC biology requires to further investigating the unique biological features of LSCs from the cellular and molecular levels. 2 , 6 These features will provide a keen insight into the dynamic state of LSCs, which is important in current leukemia research. Given that AML is a heterogeneous disease, the regulatory machinery for maintaining LSC function is extremely complicated, and involves multiple layers of alterations, such as transcription factors, metabolism, epigenetics, and microenvironments.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the relationship in its origin, LSCs share many biological features with their stem cell counterparts—normal HSPCs, thus, specifically targeting LSCs becomes a big challenging in this field. 6 We believe that key to successfully targeting LSCs is to fully understand the unique molecular mechanisms in maintaining their stemness, the core stem cell properties of self-renewal and differentiation. Herein, we will focus on discussing the biological features of AML LSCs, and pay much attention to the molecular mechanisms of stem cell maintenance.…”
Section: Introductionmentioning
confidence: 99%